Metazoários endoparasitos de Brycon orbignyanus (Characidae: Bryconinae) em uma planície de inundação neotropical. - Fernandes, Eliane da Silva (2012)
Research of species richness and composition are central themes in helminthes`community ecology, because they improve the comprehension of the factors that determine community structure. The floodplain ecosystems and the environmental alterations induced by the hydrological cycles indicate events that maintain biodiversity in time scales, as occurs on the high Paraná river floodplain, where the individuals of Brycon orbignyanus were collected. The objective of this study was to evaluate the responses, such as richness and abundance, during different hydrological cycles based on the hypothesis that the size classes of B. orbignyanus are decisive to the composition and abundance of endoparasites on different hydrological periods (high and low waters). The analised fishes showed 69.23% of prevalence, and mean abundance of 1.57, presenting 13 species of parasites from four phylum: Digenea, Cestoda, Nematoda and Acantocephala. Only the fish sizes demonstrated a positive correlation with mean diversity and abundance the endoparasites infracommunity, supporting the hypothesis that larger hosts are able to harbor a parasite infracommunity more abundant and diverse. The highest hydrological levels, which coincided with the higher temperatures, were positively correlated with overall richness and abundance of endoparasites. The diversity of habitats provided by the floodplain conditions can be considered as the main factor explaining the differences between these attributes of parasite species. Variations on the parasite richness between different hosts provide not only a good model for studies of the community diversification, but are also of great interest in the conservation of species.